A-FABP and its association with atherogenic risk profile and insulin resistance in young overweight and obese women. (October 2013) - Mankowska-Cyl, Aneta; Krintus, Magdalena; Rajewski, Pawel; Sypniewska, Grazyna
Aim: We evaluated the association of A-FABP with proatherogenic risk profile and insulin resistance (IR) in young, nondiabetic, overweight/obese women.Materials & methods: Serum A-FABP, high-sensitivity CRP, adiponectin, glucose, insulin, lipids and apolipoproteins were measured in 104 women (aged 20–45 years; BMI ≥25 kg/m 2 ) and age-matched healthy controls (n = 76; BMI <25 kg/m 2 ). All patients underwent blood pressure and anthropometric measurements.Results: A-FABP concentration was related to IR, and anthropometric and atherogenic indices. A-FABP was an independent predictor of triglyceride:high-density lipoprotein cholesterol, explaining 42% of its variation in overweight/obese women. At a cutoff level of 16 ng/ml, A-FABP discriminated between controls and overweight/obese (area under curve = 0.96) with high sensitivity and specificity. A-FABP predicted atherogenic risk, with an odds ratio of 11.2 (95% CI: 3.7–34.2), 7.1 (1.9–27.2) and 6.7 (2.6–17.2) for having elevated triglyceride:high-density lipoprotein cholesterol, apoB and CRP, respectively, and IR with an odds ratio 5.6 (1.8–17.2).Conclusion: A-FABP seems to be a valuable predictor of atherogenic risk profile; if elevated it contributes to cardiovascular disease beyond its effect on IR.